Physical Properties of Sensor Structures on the Basis of Silicon p−n Junction with Interdigitated Back Contacts - Kozynets’, O.V.; Litvinenko, S.V. (Ukrainian Journal of Physics, 2012)
The influence of the adsorption of water molecules on the photosensitivity of a silicon p–n junction with interdigitated back contacts has been studied. It has been shown that the examined structures can be used for the creation of effective chemical sensors.